Simulación multimodal del tránsito en zonas conflictivas de la ciudad de Loja - Pitisaca Díaz, Carlos Andrés (2023)
The present degree work focuses on obtaining a multimodal simulation of a central area with the congested vehicular flow in the city of Loja; this simulation was carried out by the PTV VISSIM software, the same one that allowed adding the variables involved for the analysis and management of the Vehicular flow. This project was carried out to increase the interest of Automotive Engineering students in the development of sustainable mobility projects and to propose possible solutions that can be applied to the problem of traffic in the city. The data obtained to carry out the simulation was determined by observing videos in the study area recorded during peak hours, from 7 to 9, 12 to 14 and 17 to 19 hours. The study area is by determining some factors such as traffic, a large pedestrian flow and the presence of public transport. The data are classified by types of cars, pedestrians, traffic light cycles, the total number of public transport and the total count of vehicles that travel along the avenue and secondary street. In the PTV VISSIM software, it began with the elaboration of the sections to later introduce the vehicular flow, later the pedestrian sections, the lanes for public transport and the configuration of both pedestrian and vehicular traffic lights were elaborated. The simulation obtained can be viewed and analyzed in two and three dimensions, allowing the user to have a royal perspective of what happens in the study area; and allowing the variables to be modified to generate new simulations. Finally, it has been possible to obtain a simulation that in the future could be used to develop new research and application projects around sustainable mobility. Keywords: Sustainable mobility, pedestrian flow, traffic lights, vehicular flow, types of traffic lights.